The open source guild: creating more sustainable enterprise?. Issue 1 (13th February 2017) - Larner, Justin; Cheverst, Keith; MacDonald, Matthew; Hoile, Cefn; Soutar, Angus
Abstract : Purpose: The purpose of this paper is to report on an action research project with two emergent micro-businesses that explored how their business model connected with the principles of open source. Design/methodology/approach: The authors first gained initial qualitative data to establish the core values of each micro-business, which the authors then explored in the context of open source and business models in two design workshops with each organisation. Findings: The authors developed the open source guild business model, which has the elements of: building a focal micro-business with resources secured through the guild, promoting learning and development through apprenticeship, promoting shared values through a commons of experience and capturing value by protecting key intellectual property. Research limitations/implications: This research was undertaken with two emergent micro-businesses in the North West of England. Further research will be needed to establish the wider applicability of the open source guild model. Practical implications: The open source guild model can be a mechanism for an emergent micro-business to create a community around their values and grow their business without conventional external investment of resources. Originality/value: This research contributes to the literature on business models based on open source and how these models can be sustainable in terms of the quadruple bottom line, which extends the triple bottom line to include personal values and meaning.